Intranasal administration of probiotic Lactobacillus rhamnosus GG prevents birch pollen‐induced allergic asthma in a murine model. Issue 1 (8th October 2018) - Spacova, I.; Petrova, M. I.; Fremau, A.; Pollaris, L.; Vanoirbeek, J.; Ceuppens, J. L.; Seys, S.; Lebeer, S.
Abstract: Background: There is an increasing interest in targeted application of probiotic bacteria for prevention and treatment of airway diseases, including allergies. Here, we investigated the beneficial effects of preventive intranasal treatment with probiotics Lactobacillus rhamnosus GG and L. rhamnosus GR‐1 in a mouse model of allergic asthma. Methods: Lactobacillus rhamnosus was administered intranasally eight times on days 1‐4 and 8‐11 at 5 × 10 8  CFU/dose, followed by a 2‐week asthma induction protocol with birch pollen extract on alternating days. Effects of preventive treatment were analyzed based on serum antibody levels, bronchoalveolar lavage cell counts, lung histology, lung cytokine levels, and airway hyperreactivity. Colonization and translocation of L. rhamnosus were assessed by bacterial cell counts in nasal mucosa, fecal samples, cervical lymph nodes, and blood. Binding of fluorescent L. rhamnosus to fixed murine nasal mucosal cells and airway macrophages was visualized by fluorescence microscopy. Results: Transient colonization of the murine upper airways by L. rhamnosus GG was demonstrated and was approximately ten times higher compared to L. rhamnosus GR‐1. Marked binding of fluorescent L. rhamnosus GG to murine nasal mucosal cells and airway macrophages was visualized. Preventive treatment with L. rhamnosus GG (but not L. rhamnosus GR‐1) resulted in a significant decrease in bronchoalveolar lavage eosinophil counts, lung interleukin‐13 and interleukin‐5 levels, and airway hyperreactivity. A tendency toward a decrease in serum Bet v 1‐specific immunoglobulin G1 was likewise observed. Conclusion: Intranasally administered L. rhamnosus GG prevents the development of cardinal features of birch pollen‐induced allergic asthma in a strain‐specific manner. Abstract : Intranasal Lactobacillus rhamnosus GG (but not L. rhamnosus GR‐1) pretreatment prevents the development of airway inflammation and hyperreactivity in a mouse model of birch pollen‐induced asthma, without observable side effects. Effects of intranasally administered L. rhamnosus GG are linked to a significant decrease in lung eosinophilia and lung IL‐13 and IL‐5 levels. L. rhamnosus GG adheres well to isolated murine nasal mucosa cells and airway macrophages, and can transiently colonize the murine upper airways. This is less pronounced for L. rhamnosus GR‐1.